Enhancing Mentorship Networks through the Experiences of Women Professors of Ophthalmology - Hoyer, Amanda; Randolph, Amber; Syed, Misha F.; Afkhamnejad, Elahhe; Mirza, Rukhsana G. (Journal of Academic Ophthalmology, 2023)
Purpose The aim of this study is to identify and characterize women professors in ophthalmology to enhance professional development and equity of women in academic ophthalmology.Design Cross-sectional descriptive survey study.Participants Participants in the survey were women in ophthalmology departments who have obtained full professor rank at their respective institutions.Methods A cross-sectional study was conducted using data from an electronic survey of women ophthalmologists and researchers who had obtained full professorship rank in ophthalmology. The survey included questions about degree obtained, training path, fellowship, length and trajectory of academic career, family or medical leave participation, previous positions, and mentorship involvement. Statistical comparisons were made based on response.Main Outcome Measures Survey responses to questions pertaining to three domains: education and training, academic career, and mentorship.Results Women that obtained the professor title within ophthalmology largely held Doctor of Medicine/Doctor of Osteopathic Medicine degrees, were more likely to have completed fellowship training, and on average took 11 to 15 years to obtain the full professor title. The participants held a variety of other positions and titles throughout their academic careers. The vast majority of women reported having between 1 and 3 mentors during their careers with the majority also noting they currently participate in mentoring programs. Surveys were completed by 62 (30% response rate) women full professors of ophthalmology.Conclusion The experiences women have along the academic path to professorship are described in this survey and can help to inform junior faculty. Literature review highlights the importance of mentorship for work productivity, retention, and promotion within academic medicine which is an element seen in the vast majority of our participants' career paths. Guided by the identification of women professors within departments of ophthalmology and characterization of their experiences, a new initiative called Women Professors of Ophthalmology was formed under the Association of University Professors of Ophthalmology's organizational structure in 2021. This group that is tailored for women professors of ophthalmology to foster peer mentorship and guidance is poised to increase the retention and promotion of women in academic ophthalmology.
Keywords: women; professors; academic ophthalmology; mentorship